The impact of amino acids on methane hydrate phase boundary and formation kinetics. (February 2018) - Bavoh, Cornelius B.; Nashed, Omar; Khan, Muhammad Saad; Partoon, Behzad; Lal, Bhajan; Sharif, Azmi M.
Graphical abstract: Highlights: The influence of arginine and valine on the thermodynamics and kinetics of hydrate formation was tested. Both arginine and valine shows thermodynamic inhibition but kinetically promotes methane hydrates formation. The methane hydrate boundary conditions are predicted in the presence of arginine and valine. Bothe arginine and valine significantly showed final gas consumption as compared to SDS. Abstract: The thermodynamic and kinetic effects of two amino acids (valine and arginine) on methane hydrate formation was evaluated by measuring the dissociation temperature of methane hydrate in the range of 4.5–10 MPa using the T-cycle method. The kinetics of methane hydrate formation was evaluated at 7.1 MPa and 274.15 K. The experiments were conducted at concentrations of 0.01 and 0.05 mass fraction. Both amino acids showed a slight inhibition effect on the phase boundary of methane hydrate. The predicted methane hydrate phase boundary data in the presence of amino acids was strongly correlated with the experimental data with R = 0.9996 and an AAE less than 0.15 K. However, these amino acids also showed hydrate formation rate enhancement compared to pure water. In addition, the total methane uptake at the end of the experiments was increased in the presence of these amino acids.